The Role Of Corporate Governance In Raising The Efficiency And Effectiveness Of The Internal Control Administration In Syrian Government Banks - كراز, شادي (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The study aimed to assess the status of corporate governance in government banks in the Syrian business environment and its role in raising the efficiency and effectiveness of the internal control department. The study sample included two government banks (Commercial Bank of Syria and Real Estate Bank) Both banks have reached the following results: - There is a strong and effective basis for applying the principles of governance in Syrian government banks. - There is a statistically significant relationship to the application of the principles of governance in raising the efficiency and effectiveness of internal control in Syrian government banks. - There is a statistically significant relationship to the application of the principles of governance in enhancing the confidence in the quality of accounting information in Syrian government banks. - There are no statistically significant differences on the role of governance principles in raising the efficiency and effectiveness of internal control due to the demographic variables (gender, age, academic qualification, experience) The study recommended the need to strengthen the contribution of supervisors and regulators in the development of controls that increase the efficiency of governance in a way that ensures improved internal control in Syrian government banks, in addition to conducting research and other studies; to explore more governance mechanisms that improve the effectiveness of control Syrian government banks.